Karakteristik Masyarakat Jepang - Nindya, Elizabeth Ika Hesti (Vocational College of Diponegoro University, 2017)
Characteristics of a nation is formed from the crystallization of the values that are imbued by society. This research uses a descriptive method. The character of Japanese society mostly derived from the bushidou code of ethics that is rooted and practiced since feudal times, namely integrity, honesty, courage, generosity, honor, sincerity, loyalty and loyalty. Japanese society has a habit of maintaining harmony in behaving with the aim of creating stability in society, speak vaguely to keep the other person's feelings.Moreover, the value of the shaping characteristics of Japanese society is the attitude of empathy; attitude dependent; feelings of debt; obligation to pay for services / merit; feelings of universal love.